Pengaruh Permainan Tradisional Terhadap Peningkatan Kelincahan Siswa Kelas 5 SDN 2 Cileuleuy - Maulana, Aviv Ryan; Fauzan, Elang (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study was to determine the zig-zag training on increasing agility in traditional sports games on the obstacle number. The method in this study is a type of quantitative research using an experimental method with a One Group Pretest-Posttest Design. The instrument used was the Pretest-Posttest on zig-zag agility. The data analysis technique used was the analysis prerequisite test, namely the Normality Test, Homogeneity Test, Hypothesis Test, Paired Sample T-test. This study was conducted at SD Negeri 2 Cileuleuy with a sample of 20 fifth grade students, selected by Quota Sampling. The results of this study indicate that zig-zag training has a significant effect on agility in the obstacle game, namely the fifth grade students of SD Negeri 2 Cileuleuy